Komentarz do przekładów literatury polskiej na język macedoński w 2016 roku - Tanuševska, Lidija (Przekłady Literatur Słowiańskich, 2017)
Commentary on Translations of Polish Literature in Macedonian Language Published in 2016 This text analyzes the motivation behind choosing particular books in a given period, with a special emphasis on the literary reportage, which has broken into the collective consciousness of Macedonian reading audience and now slowly gains popularity. The article also provides information on the current situation of literary translators and the publishing houses’ modes of operation What is also described here are the main determinants of literary translation, which vary in individual cases. Keywords: facts, narrative, translation, language, style